Media Development Video Tutorial Model Big Ball Game to Improve Basic Manipulative Movement Skills - Indah Verawati; Rahma Dewi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to develop a video tutorial application for the big ball game model to improve manipulative basic movement skills and be developed as a sports and learning teacher guide with the development of basic movement skills. The products produced are CDs and video tutorial manuals for big ball game models. This research was developed by adapting the research and development education model of Gall, Gall, & Borg. The development procedure used includes several stages: 1) analyzing the content of the product being developed, 2) developing the initial product of the game, 3) expert validation, 4) field testing, 5) product revision and qualitative. The results of a small group trial of 20 elementary school students at SD S Gajahmada and SDS Islam Al Ulum Terpadu obtained a percentage of 91.31% (very suitable for use) and the results of a large group trial were 40 elementary school students, SDN No:1017774, SDN No : 101775, SDN No: 101776 Medan City obtained a percentage of 93.19% with the category (Very Suitable for Use). The conclusions in this study areimproving students' basic manipulative movement skills can develop optimally with teacher creativity in developing quality learning in accordance with predetermined competency standards for elementary school students. With big ball games that are carried out, basic manipulative movement skills will increase and carry out activities happily.